Filosofia como Autoconhecimento: uma chave argumentativa para compreender o Idealismo de Hegel (Revista Eletrônica Estudos Hegelianos, 2019)
Hegel saw his own philosophy as a final point in the history of philosophy, and he certainly was right about this. This becomes clear if we look at the evolution of the dispute about self-knowledge and self-consciousness, together with their relation do knowledge in general. In Hegel’s theory, all philosophical knowledge is, finally, integrated into self-knowledge – and all normativity is integrated into self-volition. Both culminate in a concept of complete self-referentiality which comprises everything and, with this, turns out to be perfect and absolute. Such a conception may seem exaggerated, but it represents a plausible answer to a very fundamental problem of knowledge: I can never arrive from knowledge of a mere object to knowledge of myself. On the other hand, if we conceive of self-knowledge as pure self-consciousness, we can never add to it the consciousness of an external object. However, it seems evident that in our common consciousness self-consciousness and allo-consciousness are mingled: I can be conscious of myself as being conscious of an object. Therefore, self-consciousness and consciousness of objects must be originally linked to one another. As this link cannot be explained parting from the objectual side of consciousness, it must originate from its subjective side. According to Hegel, the subject develops, through the dialectical process of its self-comprehension, a self-referentiality which is discursively articulated an which accommodates within itself the reference to its other as a moment of its own dynamic. Seen like this, Hegel’s idealism seems not so much the statement of an enormous pretension, but the effort to resolve e very fundamental problem which continues valid until today.